Protection by Liquorice in Alcohol Induced Gastric Mucosa Damage - Ligha, A.E.; Fawehinmi, H.B. (Pakistan Journal of Nutrition, 2009)
Gastric diseases are widespread among the inhabitants of many countries and alcohol consumption is a known precipitating factor. This study investigates the protective effect of Liquorice, an indigenous plant in tropical and sub-tropical areas and belongs to the Fabaceae family on 80% alcohol- induce gastric mucosa lesions and morphological changes in rats. The rats were divided into five groups of five rats per group. Gastric damage was induced with 80% alcohol. The treated group received the crude extract of 200 mg/kg.oral prior to alcohol gastric mucosa damage induction. Histological studies, ulcer index, Alkaline Phosphotase (ALP), lipid peroxidation product (TBARS) which is an index of lipid peroxidation were studied. Liquorice pre-treatment showed protection against alcohol mucosa damage; a significant reduction in the ulcer index of 1.94 ±0.05 against 5.24 ±0.07 of positive control. The ALP and TBARS were also significantly reduced. The results suggest that Liquorice seed extracts have significant mucosal protective and antioxidative effects on the gastric mucosa in rats.